Steam Learning Training Through Loose Part Media in The Coastal Area - Sri Rawanti; Setiyo Utoyo; Pupung Puspa Ardini (PEDAGOGIKA, 2023)
Steam learning training through the Loose Part Media is a community service program that aims to provide education to institutions, educators and parents of students in an effort to improve the quality of education, especially early childhood education. STEAM learning for early childhood or pre-school children emphasizes more on active learning, stimulating children, solving problems, focusing on solutions, building logical and systematic ways of thinking and sharpening critical thinking skills. In optimizingtheapplication of STEAM learning, it is necessary to support adequate teaching resources, especially in the procurement of teaching media and play tools. Reviewing from the strategic location of the service located in Bone Bolango Gorontalo province which is a coastal area far from the city so that it is difficult to procure teaching media and play tools. Therefore, one of the right solutions that can support the optimization of the application of STEAM learning is the use of Loose Part media. Throughthe use of Loose Part media, institutions, educators and parents can use objects in the environment around children as teaching media and play tools.